Persepsi Masyarakat tentang Partisipasi Masyarakat dalam Pemilihan Umum 2024 di Kota Jayapura - Rhina Pongtuluran; La Juli; Dwi Puji Irjayanti (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Community participation is an important indicator of democratic success because it reflects citizens' political awareness in exercising their voting rights. This study aims to analyze public perceptions of participation in the 2024 General Election in Jayapura City and identify the factors influencing those perceptions. The study employed a qualitative approach using observation, interviews, and documentation as data collection techniques, while data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that public perceptions of participation in the 2024 General Election were generally positive and were influenced by political education, political experience, access to information, political communication, and trust in election organizers. These perceptions encouraged citizens to exercise their voting rights consciously, rationally, and responsibly. The study concludes that public perception is a key factor in improving the quality of political participation in Jayapura City. The novelty of this study lies in its analysis of the relationship between public perception, voting behavior, trust in election organizers, and participatory oversight as an integrated framework for explaining the quality of political participation in the 2024 General Election.